2017
DOI: 10.1097/iae.0000000000001175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Lamina Cribrosa Thickness of Patients With Unilateral Branch Retinal Vein Occlusion and Healthy Subjects

Abstract: A thinner LC was observed in both eyes of unilateral BRVO patients compared with those of healthy subjects. This finding suggests that thin LC may contribute to the pathogenesis of BRVO as a local mechanical factor in addition to systemic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Our findings were consistent with previous findings, which indicated that there are similarities in the changes in the parapapillary area and ONH between patients with BRVO and glaucoma. [3][4][5][6][7][8] The finding of significant thinning of the mean PCT in the eyes with focal LC defects in both the BRVO and glaucoma groups supports the hypothesis that vascular insufficiency is, to some extent, involved in the pathophysiology of these two diseases. The short posterior ciliary artery (SPCA) supplies blood to the posterior choriocapillaries, from the macular to the equator and the peripapillary areas.…”
Section: Plos Onesupporting
confidence: 61%
See 3 more Smart Citations
“…Our findings were consistent with previous findings, which indicated that there are similarities in the changes in the parapapillary area and ONH between patients with BRVO and glaucoma. [3][4][5][6][7][8] The finding of significant thinning of the mean PCT in the eyes with focal LC defects in both the BRVO and glaucoma groups supports the hypothesis that vascular insufficiency is, to some extent, involved in the pathophysiology of these two diseases. The short posterior ciliary artery (SPCA) supplies blood to the posterior choriocapillaries, from the macular to the equator and the peripapillary areas.…”
Section: Plos Onesupporting
confidence: 61%
“…If both BRVO and glaucoma share a common pathophysiologic change that affects the parapapillary area and the ONH, the findings of previous studies can also be explained more easily. [3][4][5][6][7][8] However, further prospective studies are needed to determine the specific pathophysiologic mechanism associated with peripapillary choroidal change and focal LC defects in patients with BRVO.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…First, the number of study subjects was limited. Second, we did not include BRVO patients with occlusions at the optic disc (although the prevalence is considered to be relatively lower than that of BRVO occurring at AV crossings) 37 or patients with poor visual function due to severe BRVO. Therefore, the current findings may not be generalizable to all types of BRVO.…”
Section: Discussionmentioning
confidence: 99%